2016
DOI: 10.5455/ijmsph.2016.25122015325
|View full text |Cite
|
Sign up to set email alerts
|

Study on awareness about vector borne diseases and education about preventive measures in rural field practice areas of Kurnool medical college, Kurnool

Abstract: Background: Vector borne diseases (VBDs) account for 17% of the estimated global burden of all infectious diseases. The most deadly VBD, malaria caused an estimated 627,000 deaths in 2012. The world's fastest growing VBD is dengue, with a 30-fold increase in disease incidence over last 50 years. Objective: To create awareness about common VBDs in the villages through village volunteers and educate them about the measures to prevent the occurrence of the disease by community participation and behavioral change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Majority of ASHA's had knowledge about symptoms of DF, mode of transmission, breeding sites of mosquitoes, etc., similar results to the other studies whereas only 30.72% knew the danger signs of dengue which is very essential for early referral to hospital to prevent complications and deaths due to dengue, this aspect has been enhanced and given importance in guidelines for reporting of an outbreak of dengue [6,14] and these results indicate that this aspects needs to be stressed in their training program. [15,11] Although the study showed 143 (86.1%) practiced complete preventive measures, nearly 15% of the ASHA workers were lacking in that, hence there is need for reinforcement in the training sessions. [15,14] One of the important factor influenced was about one-fourth of the workers complained that there was lack of community participation in implementation of control measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of ASHA's had knowledge about symptoms of DF, mode of transmission, breeding sites of mosquitoes, etc., similar results to the other studies whereas only 30.72% knew the danger signs of dengue which is very essential for early referral to hospital to prevent complications and deaths due to dengue, this aspect has been enhanced and given importance in guidelines for reporting of an outbreak of dengue [6,14] and these results indicate that this aspects needs to be stressed in their training program. [15,11] Although the study showed 143 (86.1%) practiced complete preventive measures, nearly 15% of the ASHA workers were lacking in that, hence there is need for reinforcement in the training sessions. [15,14] One of the important factor influenced was about one-fourth of the workers complained that there was lack of community participation in implementation of control measures.…”
Section: Discussionmentioning
confidence: 99%
“…[15,11] Although the study showed 143 (86.1%) practiced complete preventive measures, nearly 15% of the ASHA workers were lacking in that, hence there is need for reinforcement in the training sessions. [15,14] One of the important factor influenced was about one-fourth of the workers complained that there was lack of community participation in implementation of control measures. Similar observation was noticed Malhotra and Kaur study, [4] Kohli et al study in Delhi, [10] and Sreedevi et al study in Karnool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria, the most deadly VBD, caused an estimated 627,000 deaths in 2012. 1 Though several measures for their prevention and control are followed, yet the problem density is too high with 300-500 million cases and 1.1-2.7 million deaths due to malaria alone globally per year. 2 Out of six vector borne diseases, malaria, filariasis, Japanese encephalitis, dengue and chickengunya are transmitted by different kind of vector mosquitoes, while kala azar is transmitted by sand flies.…”
Section: Introductionmentioning
confidence: 99%
“…6 In a study conducted by Sreedevi et al, in Kurnool found that only 32% of the population had knowledge about diseases spread by mosquitos. 7 When asked about symptoms, 52.5% i.e. 136 of the subjects could name at least one symptom and 47.5% had no knowledge of any symptoms.…”
mentioning
confidence: 99%